IDENTIFIKASI AKTIVITAS PEREKONOMIAN MASYARAKAT SEKITAR PELABUHAN AMURANG - Valentine Prilly Kesek; Celcius ., Talumingan; Caroline B. D. Pakasi (AGRI-SOSIOEKONOMI, 2017)
This study aims to determine the activities of the Amurang Port on the economy of the communities around the harbor. This research was conducted at the Amurang, Sub-district of West Amurang, South Minahasa Regency. The method used in this study is a qualitative research method. The reason for using qualitative methods for this research seeks to find answers to questions relating to the socio-economic life of the commonity who are residing around the port. The data used are primary data and secondary data. Data was collected by using observation, interview and documentation. The research found that the activities in Amurang Port can increase the income of local communities, opening up a new business thus increasing employment absortion, there are trading activities and there are social-economic activities around the harbor. Thus the presence of the Amurang Port has a positive impact for the people that are around the port Amurang form of employment absortion and increased income of communityKeywords : identification, economic activities, the Amurang Port, Sub-district of WestAmurang, South Minahasa District